Pola Kesantunan Berbahasa Tindak Tutur Direktif dalam Interaksi Belajar Mengajar di SMP Negeri 4 Sungai Penuh - Maiza, Suci (Universitas Tidar, 2021)
Abstrac The politeness in directive speech act is an important thing in teaching and learning interactions. Therefore, it is necessary to study to the use of directive speech acts spoken by teachers and students in teaching and learning interactions. This study aimed to describe the forms, functions, and causative factors of the politeness in directive speech act in teaching and learning interactions at SMP Negeri 4 Sungai Penuh.This research is a qualitative-descriptive research using the technique of Simak Bebas Libat Cakap. Data were collected by recording and questionnaire. The theory used as the basis for analyzing the politeness in directive speech act in this research was the pragmatic theory of Searle, Yule George (1996), Geoffrey Leech (1993), Abdul Chaer (2010), and Ibrahim (1993).The results showed that the forms of the politeness in directive speech act in teaching and learning interactions at 4 Public Junior High School Sungai Penuh were the forms of requests, questions, orders, prohibitions, giving permission and advice. The functions of the politeness in directive speech act were the functions of asking, requesting, willing, prohibiting, pressing, directing, allowing, instructing, advising, suggesting, demanding, inviting, requiring, and forgiving. The causative factors of the politeness in directive speech act were the context, intonation, social institutions, diction, topics of conversation, and language style.